Perubahan Warna Permukaan Resin Komposit Nanohybird Pasca Perendaman Dalam Cuko Pempek - Khoirunnisa, Nabila Farah; Budiono, Budiono; Jayanti, Lira Wiet (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2019)
The development of science, technology and patient demands regarding restorative materials that are colored with teeth is currently higher. Dental-colored restoration materials are widely used, one of which is nanohybrid composite resin. The nanohybrid composite resin has a small and fine particle size of 0.04 um. Nanohybrid composite resins have many advantages, but they also have the disadvantage of liquid absorption properties which can cause discoloration. One of the liquids that cause discoloration is cuko pempek. Objective: To find out the surface color changes of nanohybrid composite resin after immersion in cuko pempek. Methods, an experimental laboratory study with a pre and post test only group design study design. Sample 16 pieces of nanohybrid composite resin measuring 10 x 2 mm. The sample was immersed using pempek cuko as much as 5 ml with a temperature of 37oC for 7 days. Color change is measured with a spechtrophotometer (UV-2401 PC). Results, there was a change in the surface color of nanohybrid composite resin soaked with pempek cuko which marked an average increase in dE*ab before immersion (18.5925) and after immersion (23.3169) with a difference of 4.7844. The paired t test results also showed a significant color change that is p = 0,000 (p <0.05). Conclusion, there is a change in the surface color of the post-immersion nanohybrid composite resin in pempek cuko.